PROYEKSI AKUNTABILITAS KEUANGAN SERTA IMPLIKASINYA TERHADAP KINERJA PERGURUAN TINGGI SWASTA - Ade Widiyanti (TECHNOBIZ : International Journal of Business, 2022)
This study aims to examine and analyze the effect of the implementation of the internal quality assurance system, the implementation of the accounting information system and the commitment of the foundation leadership to financial management accountability and its implications for the performance of the tridharma of private universities. The object of research is private universities under the Regional IV Higher Education Service Institute for West Java and Banten (LLDikti IV). The sample used in the study was 219 universities. The data was obtained by distributing questionnaires to the respondents, namely the leaders of private universities in the LLDikti IV area. Data were analyzed using structural equation modeling (SEM). There is no significant effect between the implementation of the internal quality assurance system and financial management accountability (2) there is a positive and significant effect between the implementation of the internal quality assurance system and the performance of the higher education tridharma (3) there is a positive and significant effect between the implementation of the accounting information system and financial management accountability (4) there is no significant effect between the implementation of the accounting information system and the performance of the higher education tridharma (5) there is no significant effect between the commitment of the foundation leadership and financial management accountability (6) there is a positive and significant effect between the commitment of the foundation leadership and the performance of the higher education tridharma (7) there is a positive and significant effect between financial management accountability and the performance of higher education tridharma